Assessing climate risks across different business sectors and industries: an investigation of methodological challenges at national scale for the UK. (30th April 2018) - Surminski, Swenja; Di Mauro, Manuela; Baglee, J. Alastair R.; Connell, Richenda K.; Hankinson, Joel; Haworth, Anna R.; Ingirige, Bingunath; Proverbs, David
Abstract : Climate change poses severe risks for businesses, which companies as well as governments need to understand in order to take appropriate steps to manage those. This, however, represents a significant challenge as climate change risk assessment is itself a complex, dynamic and geographically diverse process. A wide range of factors including the nature of production processes and value chains, the location of business sites as well as relationships and interdependencies with customers and suppliers play a role in determining if and how companies are impacted by climate risks. This research explores the methodological challenges for a national-scale assessment of climate risks through the lens of the UK Climate Change Risk Assessment (UKCCRA) process and compares the approaches adopted in the first and second UKCCRA (2011, 2016), while also reflecting on international experiences elsewhere. A review of these issues is presented, drawing on a wide body of contemporary evidence from a range of sources including the research disciplines, grey literature and government policy. The study reveals the methodological challenges and highlights six broad themes, namely scale, evidence base, adaptation responses, scope, interdependencies and public policy. The paper concludes by identifying suitable lessons for future national climate risk assessments, which should guide the next phase of research in preparation for UKCCRA3 and those of national-level risk assessments elsewhere. This article is part of the theme issue 'Advances in risk assessment for climate change adaptation policy'.